If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2a + 6) = 3(4a + -8) Reorder the terms: 4(6 + 2a) = 3(4a + -8) (6 * 4 + 2a * 4) = 3(4a + -8) (24 + 8a) = 3(4a + -8) Reorder the terms: 24 + 8a = 3(-8 + 4a) 24 + 8a = (-8 * 3 + 4a * 3) 24 + 8a = (-24 + 12a) Solving 24 + 8a = -24 + 12a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-12a' to each side of the equation. 24 + 8a + -12a = -24 + 12a + -12a Combine like terms: 8a + -12a = -4a 24 + -4a = -24 + 12a + -12a Combine like terms: 12a + -12a = 0 24 + -4a = -24 + 0 24 + -4a = -24 Add '-24' to each side of the equation. 24 + -24 + -4a = -24 + -24 Combine like terms: 24 + -24 = 0 0 + -4a = -24 + -24 -4a = -24 + -24 Combine like terms: -24 + -24 = -48 -4a = -48 Divide each side by '-4'. a = 12 Simplifying a = 12
| 33=-4x+5 | | 2(x+3)+3x-x=x+16 | | 10=11+11y | | 5c+13=16 | | 25-7a=28a-4a | | f(2)=3x*2-3x-3 | | 15x-5y+18=20 | | 9q-24=9q-12 | | 6cos^2x-7cosx-3=0 | | 5x+35=135 | | 5.8z-5=4.8z-5 | | 2x+x+3=3x+5 | | -5x-7=9x+15 | | -7-8n=47 | | 5=18 | | 3(-x)+5x=x+9 | | 2(-x)+5x=x+9 | | .1x=-13 | | (12x-30)+3x=180 | | -65-12x+8x=55 | | 2x+3x-40=50 | | ab+bc+ac=-abc | | -19-2x+4x=7 | | 5X-(3)+(-9)=4x-(-7+1) | | ab+bc+ac=1110 | | 2(x+4)+4x-x=2x+20 | | -26-5b=4-7b | | 7+9-3b+20= | | 16-2x=4x | | 6r^2+8r-20=5r^2 | | -91+x+8x=35 | | 2m^2+2m-12=12 |